A retrospective cross-sectional study of nonsurgical management of childhood intussusception in a tertiary care hospital - Muduli, Jayant Kumar; Mitra, Meenakshi (Indian Journal of Child Health, 2022)
Objective: To describe the factors based on which nonsurgical management of acute intussusception may be undertaken. Methodology: A retrospective cross-sectional study was conducted by collecting data of all the children admitted in the pediatric ward of the hospital with radiologically confirmed intussusception between January 2016 and December 2016 from case files. A surgical consultation had been taken, and the children with no hemodynamic instability had been treated with gut rest, intravenous fluids, and sodium phosphate enema. Results: Total 25 cases were studied, and nonsurgical management was successful in 88% of these cases. Statistically significant association was found between younger age (p=0.033), shorter duration of symptoms at presentation (p=0.005), early initiation of treatment (p=0.001) and shorter hospital stay (p=0.002), and successful nonsurgical management of acute intussusception. Conclusion: Younger age, shorter duration of symptoms, and early initiation of management are significantly associated with successful nonsurgical management of acute intussusception. With the above results, risk stratification may be proposed for predicting successful nonsurgical management of acute intussusception.